Nano Generalized Closed Sets in Nano Bitopological Space - K. Bhuvaneswari; K. Karpagam (International Journal of Mathematics And its Applications, 2016)
The basic objective of this paper is to introduce and investigate the properties of Nano (1,2)* generalized closed sets in Nano Bitopological Spaces which is the extension work of Nano closed sets introduced by K. Bhuvaneswari et.al [1] also further investigated the properties of Nano generalized closed set in Nano bi topological space.